The Pamphagidae (Orthoptera) from East Algeria and description of a new species - Benkenana, Naima; Harrat, Abboud; Petit, Daniel (Zootaxa, 2012)
Through a 3-year survey of 9 stations in North East of Algeria, we recorded 16 species of grasshopper belonging to thefamily Pamphagidae. The National Park of Belezma, near Batna city, appears to be the richest region for this family, with10 species. Notably, Paracinipe sulphuripes, only known from Djelfa, is present at Belezma, showing unexpected rela-tionship between these two areas, separated by 280 km. Within the Pamphagus djelfensis complex, a new species is de-scribed, P. batnensis Benkenana & Petit, easily distinguishable by its epiphallic characters. Taking into account severalstudies dealing with other Algerian stations, we provide certain climatic constraints of most species, as illustrated by bio-climagrams. We show that the semi-arid stage with fresh winter and sub-humid stage with cold winter correspond to the most suitable conditions for this family.